Anthropometric Predictors in Assessment of Metabolic Syndrome among Obese Adults - Vijayalaxmi Mangasuli; Mayur S Sherkhane (Medsci Publications, 2020)
Background: Central obesity is the important risk factor in metabolic syndrome which is in turn cardiovascular risk factor which will increase the morbidity and mortality. The study was conducted to assess the anthropometric indices in predicting metabolic syndrome among obese adults. Methods: Cross sectional study was done among 264 adults having BMI more than 35 and visiting our hospital for a period of three months were included. A predesigned and pretested proforma was used to collect data. Anthropometric measurements, Blood pressure and diabetic profile was measured. Data was analysed using SPSS. Results: Among 264 adults, 118 (44.69%) had metabolic syndrome; Majority belonged to 30- 39 years (40.15%); educated up to PUC (32.58%) and belonged to class II socio-economic status (38.64%). There was significant mean difference between waist circumference, diastolic blood pressure, HDL levels and FBS levels among the study participants who had and who didn't have metabolic syndrome. Area under curve (AUC) for waist: height ratio was 0.969, whereas for waist circumference and BMI it was 0.956 and 0.689 respectively. Conclusion: Waist: height ratio can predict metabolic syndrome better than waist circumference and BMI. Central obesity should be identified at the earliest than general obesity. So that lifestyle modifications can be advised in early life to avoid further morbidity leading to further permanent disabilities and life threatening events in future.